Express (3-5x)/(x+3)^2 in the form A/(x+3) + B/(x+3)^2

A needs to be multiplied up by x+3 to make the fraction have the same in denominator as the other expressions. Then you need to equate the numerators. 3 - 5x = A(x+3) + B
You can gain two simultaneous equations from this equation, those with an x multiplier and those without:-5 = A3 = 3A + Binput A:3 = -15 + B
rearrange to find B.
Answer is therefore: 18/(x+3)^2 - 5/(x+3)

Related Maths A Level answers

All answers ▸

Why can't you divide something by 0?


Solve ln(2x-3) = 1


Show that sqrt(27) + sqrt(192) = a*sqrt(b), where a and b are prime numbers to be determined


Find the area under the curve y = sin(2x) + cos(x) between 0 and pi/2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences